2020
DOI: 10.3390/pharmaceutics12060507
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Polyplexes Mediated Transfection of Runx2-shRNA Mitigates the Osteodifferentiation of Human Valvular Interstitial Cells

Abstract: Calcific aortic valve disease (CAVD) is a progressive disorder that increases in prevalence with age. An important role in aortic valve calcification is played by valvular interstitial cells (VIC), that with age or in pathological conditions acquire an osteoblast-like phenotype that advances the disease. Therefore, pharmacological interventions aiming to stop or reverse the osteoblastic transition of VIC may represent a therapeutic option for CAVD. In this study, we aimed at developing a nanotherapeutic strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Considering that the osteoblastic differentiation of VICs leads to aortic valve calcification and the role of Runx2 in the process, we have developed a nanotherapeutic strategy targeted to prevent the phenotipic differentiation of human aortic VICs into osteoblast‐like cells in diabetic and pro‐osteogenic conditions. 75 We designed nanocarriers to silence Runx2, namely fullerene (C60)‐polyethyleneimine (PEI)/short hairpin (sh)RNA‐Runx2. We reported that these nanocarrriers efficiently downregulate Runx2 mRNA and protein expression leading subsequently to a significant reduction in the expression of osteogenic proteins (i.e.…”
Section: New Therapeutic Approaches For Aortic Valve Disease In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the osteoblastic differentiation of VICs leads to aortic valve calcification and the role of Runx2 in the process, we have developed a nanotherapeutic strategy targeted to prevent the phenotipic differentiation of human aortic VICs into osteoblast‐like cells in diabetic and pro‐osteogenic conditions. 75 We designed nanocarriers to silence Runx2, namely fullerene (C60)‐polyethyleneimine (PEI)/short hairpin (sh)RNA‐Runx2. We reported that these nanocarrriers efficiently downregulate Runx2 mRNA and protein expression leading subsequently to a significant reduction in the expression of osteogenic proteins (i.e.…”
Section: New Therapeutic Approaches For Aortic Valve Disease In Diabetesmentioning
confidence: 99%
“…Importantly, new nanocarriers aiming to block the shift of VICs to an osteoblastic phenotype were tested and found to be efficient in vitro; these results pave the way to the development of nanotherapies for CAVD. 75 Another potential promise for treatment of CAVD is the recently emerged stem cell therapy. In addition, tissue engineering of AV attains continuously new improvements.…”
Section: Future Challenges and Opportunitiesmentioning
confidence: 99%
“…Moreover, it assembles DNA in polyplexes that are stable in physiological conditions while being prone to replisomes-triggered degradation. Therefore, cationic, water-soluble, linear, and branched PEI frameworks are considered by many the gold standard in DNA and RNA delivery, both in vitro and in vivo [117,118]. The major drive in the PEI-based vectors research is the quest for additional building blocks that allow modified PEI architectures with enhanced transfection and low cytotoxicity.…”
Section: Polymeric Non-viral Vectors For Gene Deliverymentioning
confidence: 99%
“…These positive results could be further exploited by including C60 in the aforementioned supramolecular dynamic strategy that was based on libraries of modular carrier frameworks. Moreover, it has already become clinically relevant after its successful use in the delivery of Runx2-shRNA plasmids as to down-regulate the expression of proteins that are involved in the osteodifferentiation of human valvular interstitial cells in diabetic and pro-osteogenic conditions [118].…”
Section: Polymeric Non-viral Vectors For Gene Deliverymentioning
confidence: 99%
“…Thus, we hypothesized that the silencing of Runx2 using RNAi will interfere with the osteoblastic phenotypic shift of VIC and the progress of CAVD. In a previous study, we reported that fullerene (C60)-polyethyleneimine (PEI)/short hairpin (sh)RNA-Runx2 nano-polyplexes efficiently down-regulate Runx2 mRNA and protein expression, and subsequently, significantly reduce the expression of osteogenic proteins (i.e., ALP, BSP, OSP, and BMP4) in osteoblast-differentiated VIC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%